Outcomes of Laparoscopic Intra-Peritoneal Onlay Mesh with fascial repair (IPOM +) Using Composite Mesh for the Treatment of Ventral Hernias (The Planet, 2022)
Background: Ventral hernias are a common occurrence, incisional hernias being the most common, developing in up to 20% of laparotomy incisions. Numerous studies indicate that laparoscopic approach is safe and effective, and may be superior to open repair with regard to lower rates of recurrence, wound infection, greater patient acceptance, shorter hospital stay and early return to work. Objective: This study is designed to analyze outcome, complications, postoperative pain & patient compliance in laparoscopic ventral hernia repair by laparoscopicintraperitonealonlay mesh with facial repair (ipom plus) technique, using composite mesh. Materials and Methods: This was a prospective study of patients diagnosed to haveventral hernia admitted to Border Guard Hospital Dhaka for elective laparoscopic ventral hernia repair by ipom plus technique between January 2018 to December 2020.Post-operatively patients were evaluated for outcomes in sense of effectiveness, pain and complications. Results: Of the 30 patients, 17(56.7%)incisional hernias, 6(20%) paraumbilical hernias, 5(16.7%) umbilical hernia & 2(6.7%) had epigastric hernia. The mean age of the patients were40 years. Female to male ratio was 1.5 :1.Average defect size was 4.2 cm. Mean operative time was 59.6 min. Mean post-op hospital stay was 5.16 days. Average duration forpost-operative pain was 5.2 days. Intensity of pain by VAS pain score was 4± 0.49, 2.7± .65,0.82± 0.8 after 24 hours, 1 week and 4 weeks respectively.No conversion to open laparotomy was required. Reported complications were post-operative ileus 1(3.3%), seroma 2(6.7%), surgical site infection 2(6.7%) over one year of follow up. Conclusion: Laparoscopic ventral hernia repair with IPOM plus technique using composite mesh has good & efficient outcomes in terms of effectiveness and postoperative complications with satisfactory patient compliance.
Keywords: Ventral hernia; IPOM Plus